Strategi Kegiatan Madrasah Diniyah Islamiyah Babakan dalam Menanamkan Karakter Religius Siswa di MI Islamiyah Babakan Lebaksiu Kabupaten Tegal - Aris, Aris Munandar (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2023)
The problem of character is one of the problems that always concerns every nation. The occurrence of a degradation of character values or the loss of a character will certainly be a setback for every nation. One of the characters that must be embedded is religious character which is the attitude and responsibility of a person towards his god. MI Islamiyah Babakan has anticipated this by collaborating with Madrasah Diniyah Islamiyah in instilling religious character to its students. This study aims to: (1). To find out the strategy of religious character formation through the Diniyah Madrasah program. (2). To find out the strategy plan for students' religious character through the Diniyah program at MI Islamiyah Babakan Lebaksiu Tegal. This research uses a qualitative approach. Data collection by researchers using interviews, observations and documentation. The results of this study indicate that the implementation of madrasah diniyah activities at Madrasah Ibtidaiyah Islamiyah has two activities, namely reading and writing the qur'an and strengthening lessons. Each activity nurtures different religious character values. Both activities give birth to the character of love for the Qur'an, ruhul jihad or a soul that always wants to strive, likes to worship and has morals.